ANALISIS PERBANDINGAN BANK UMUM SYARIAH DENGAN UNIT USAHA SYARIAH DARI ASPEK EFISIENSI, KUALITAS ASET, DAN STABILITAS KEUANGAN - Pratiwi, Renita; Mahrus, Moh.; Candra, Alias (Indonesian Scientific Journal of Islamic Finance, 2022)
The background of this research is the measurement of efficiency in Islamic banks is an important indicator in seeing the ability of Islamic banks to survive in the face of intense competition in the Islamic banking industry as well as competition in the national banking industry in Indonesia. The asset quality of a bank shows the soundness of the bank as an intermediary in increasing public trust in banks in managing public funds. Given that asset is an important issue for banks to prevent bankruptcy and bank risk generally come from weak assets. Maintaining bank financial stability is also very important, where profit as the main source of bank funds in increasing core capital is highly dependent on the ability of the bank’s business profitability to increase profits. The study aims to the similarities and differences in efficiency, asset quality, and financial stability between Islamic Commercial Banks and Sharia Business Units for the 2016-2020 period. Data analysis method used descriptive statistical test and independent sample t-test with the help of IBM SPSS Statistic 22 software. The results of this study indicate that is a difference in efficiency, this is evidenced by the t count value of 4.379 and a significance value of 0,000 < 0,05. There are similarities in asset quality, this is evidenced by the t count value and a significance value of 0,197 > 0,05. And there are differences in financial stability, this is evidenced by the t count value of -2.180 and a significance value of 0,032 < 0,05.